Conservative therapy for extensive laryngotracheal stenosis after severe inhalation injury in a patient with severe intellectual disabilities: A case report - Tatsunori Nagamura; Takero Terayama; Hiroshi Kato; Nobuaki Kiriu; Masahiko Seki; Kohei Yamada; Soichiro Seno; Yasumasa Sekine; Kosuke Uno; Koji Araki; Tetsuro Kiyozumi (Elsevier, 2024)
Introduction: Laryngotracheal stenosis after inhalation injury can occur not only in the acute period but also in the late period. Stenosis usually develops in only one area and, in some cases, may require intubation or tracheostomy. However, selecting the treatment for extensive laryngotracheal stenosis in patients with severe mental retardation may be difficult. Case presentation: A 20-year-old man with severe intellectual disabilities was admitted to our emergency department with burns on the face and lower limbs. Severe inhalation injury was suspected; therefore, intubation was performed. The patient was extubated on day 14; however, extensive laryngeal stenosis from the supraglottic area to the cricothyroid ligament area developed on day 37, resulting in carbon dioxide narcosis requiring cricothyrotomy. We believed that the risk of re-stenosis was high, and his mental retardation would make postoperative management difficult; therefore, we selected conservative therapy. Extensive stenosis persisted over 2 years after injury with a tracheostomy tube. Conclusion: Given the risk of re-stenosis, conservative therapy or laryngotracheal reconstruction is preferred for the treatment of extensive laryngotracheal stenosis after inhalation injury. Conservative therapy is advisable when patients cannot comply with the rest required for the treatment.